Direct structural analysis of modified RNA by fluorescent in-line probing - Strauß, Benjamin; Nierth, Alexander; Singer, Marco; Jäschke, Andres (Nucleic acids research, 2012)
Abstract. Chemical probing is a common method for the structural characterization of RNA. Typically, RNA is radioactively end-labelled, subjected to probing c
Published online 14 September 2011
Gesehen am 26.08.2020